Identification of Epigenetically Modified Hub Genes and Altered Pathways Associated With Retinoblastoma - Karmakar, Aditi; Ahamad Khan, Md. Maqsood; Kumari, Nidhi; Devarajan, Nalini; Ganesan, Senthil Kumar (Frontiers in Cell and Developmental Biology, 2022)
Retinoblastoma (Rb) is the most common childhood malignancy initiated by biallelic mutation in RB1 gene and driven by various epigenetic events including DNA methylation and microRNA dysregulation. Hence, understanding the key genes that are critically modulated by epigenetic modifications in RB1−/− cells is very important to identify prominent biomarkers and therapeutic targets of Rb. In this study, we for the first time have integrated various Rb microarray NCBI-GEO datasets including DNA Methylation (GSE57362), miRNA (GSE7072) and mRNA (GSE110811) to comprehensively investigate the epigenetic consequences of RB loss in retinoblastoma tumors and identify genes with the potential to serve as early diagnostic markers and therapeutic targets for Rb. Interestingly, the GEO2R and co-expression network analysis have identified three genes namely E2F3, ESR1, and UNC5D that are significantly deregulated by modified DNA methylation, mRNA and microRNA expression in Rb tumors. Due to their recognition in all epigenetic, transcriptomic, and miRNA datasets, we have termed these genes as “common genes”. The results of our integrative bioinformatics analysis were validated in vitro by studying the gene and protein expression of these common genes in Y79, WERI-Rb-1, Rb cell lines and non-tumorigenic retinal pigment epithelial cell line (hTERT-RPE). The expression of E2F3 and UNC5D were up-regulated and that of ESR1 was down-regulated in Rb tumor cells when compared to that in non-tumorigenic hTERT-RPE cells. More importantly, UNC5D, a potent tumor suppressor gene in most cancers is significantly up-regulated in Y79 and Weri Rb1 cells, which, in turn, questions its anti-cancer properties. Together, our study shows that E2F3, ESR1, and UNC5D may be crucially involved in Rb tumorigenesis and possess the potential to act as early diagnostic biomarkers and therapeutic targets of Rb.